Model of a non-isothermal stationary magma flow in a volcanic conduit taking into account slip boundary conditions at the conduit wall - Barmin, Alexey Alexeevich; Melnik, Oleg Edwardovich; Skulskiy, Oleg Ivanovich (Computational Continuum Mechanics, 2012)
The model of a non-isothermal magma flow in a circular cylindrical volcanic conduit is proposed. It is assumed that magma viscosity depends on temperature, deformation rate and concentration of dissolved gases, which in turn depends on pressure. The possibility of the slip of magma along the conduit walls in accordance with the experimentally determined law is taken into account. An algorithm and a computational procedure for simulation of the non-isothermal stationary flow of nonlinear viscous incompressible magma in the conduit are developed. It is shown that viscous dissipation and wall slip lead to much higher discharge rates for fixed magma chamber pressure.
Keywords: magma; extrusion eruption; axisymmetrical model; non-Newtonian viscosity; wall slip; finite element method